Experimental study on blasting fracture and stress wave propagation characteristics of hard rock under different boundary conditions - Nao Lv; JiChao Duan; HaiBo Wang; XiaoHong Zhou; BaoLiang Zhou (AIP Advances)
This investigation systematically explores the impact of heterogeneous boundary constraints on fracture mechanisms and stress wave dynamics in rock specimens with central boreholes subjected to blasting loads. By altering the filling medium (air, coal, or mortar) inside a steel cylinder, six small-scale blasting experiments were conducted. Using FrcPaQ technology and high-speed strain equipment, the analysis focused on fracture features, crack distribution, and stress wave propagation patterns, highlighting the key role of boundary conditions in determining blasting outcomes. Results revealed a significant correlation between crack formation in specimens and the boundary conditions of the rock samples. Specimens with gaps exhibited random cracks and extensive fragmentation. Conversely, in closed samples, the filling medium acted as a weak structural plane, directing cracks toward it. As the wave impedance of the filling medium increased, both the number and extension distance of radial cracks decreased, thereby mitigating overall sample failure. The propagation of elastic waves within the samples was also influenced by boundary conditions. Surface strain decreased with increasing wave impedance of the filling medium, while the maximum strain recorded on the steel cylinder correspondingly increased.